Prototype of Water Rise Detection Tool in Kampar River Fish Cages Based on Internet of Things (IoT) - Setiawan, Muhammad Bayu; Azriadi, Emon; Joko Musridho, Raja (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Fish cages, classified as vessels under the Indonesian Shipping Law Number 17 of 2008, must consider safety aspects due to risks such as sinking and drifting. Increasing river discharge causes damage to the cage structures, potentially worsening fish health and causing economic losses for fish farmers. This study aims to develop a water level detection device for fish cages in the Kampar River using Internet of Things (IoT) technology based on waterproof ultrasonic sensors and the ESP32 microcontroller. The device can automatically monitor water levels and provide real-time alerts to cage owners via wireless Wi-Fi or Bluetooth connections. The research uses a Research and Development (R&D) approach. This innovation is expected to help fish cage owners anticipate risks from changes in water levels and improve the management of fish farming operations